Parenting Styles of Adolescents’ Parents in Kosovo and Metohija - Pavićević, Miljana; Minić, Jelena (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
Based on the summary of the findings of research on parenting styles, which was conducted on the sample of adolescents living or studying in Kosovo and Metohija, the paper aims to present predominant parenting styles and foresee further development of certain traits analysed in adolescents. Furthermore, not only does it aim to specify the direction of certain surveys on this issue in the future but also put forward recommendations relating to organizing prevention and intervention programmes intended for parents and adolescents. After gaining an insight into the findings of surveys presented (conducted between 2012 and 2019), the following predominant parenting style stood out among the adolescent respondents (more than 2200 adolescents, i.e., high school students and undergraduates aged between 16 and 24): the cold parenting style is prevalent in fathers in every survey presented, while the warm parenting style is prevalent in mothers, in addition to the cold parenting attitude. The research on parenting styles has yielded certain correlations and differences, as well as the findings highlighting the possibility of predicting development of specific traits in adolescents depending on parenting styles. The conclusions are arrived at have contributed to producing recommendations on how future surveys are to be organized and conducted.   The recommendations relating to working with parents are as follows: organizing educational seminars for parents for the sake of their familiarizing with and learning about quality parenting styles. These educational seminars should involve acquisition communication skills with the aim of more effective communication and better relationship between parents and adolescents. Moreover, providing families with counselling is recommended with a view to strengthening capacities for cooperation with parents in terms of their parenting styles and child care.    It is of paramount importance to exert influence on fathers, whose education would enhance the level and quality of their involvement in parenting. Involving parents in further research is imperative, with the aim of comparing the findings relating to parents’ standpoints and their children, and examining the relation among parenting styles, age, and a range of family variables
Keywords: parenting styles; parents; high school students; undergraduates